The role of women in British society during the Second World War and its after-effects - Vlčková, Eva (2007)
This thesis discusses the position of women in Britain during the Second World War and its after-effects. At the beginning of the war men left for the fighting and workers were greatly needed. What seemed to be unreal in the past now became reality - women were needed as labour force. They served in the services and they also carried out hard and dangerous work on the home front. For women a new period of their lives started. At the end of the Second World War, however, women found that the advances they had made were greatly reduced when the soldiers returned from the battlefields. At the end of the Second World War, those women who had found alternate employment lost their jobs. The returning soldiers had to find jobs and many wanted society to return to normal. But the six years of the war conflict were a breath of fresh air in Britain in terms of gender stereotypes and women became more emancipated and self-sufficient and so they started to defend their rights. The seed of the seco